Identifying the top research priorities in medically not yet explained symptoms (MNYES): a James Lind Alliance priority setting partnership. Issue 7 (1st July 2022) - van der Feltz-Cornelis, Christina Maria; Sweetman, Jennifer; Edwards, Mark; Gall, Nicholas; Gilligan, Jennifer; Hayle, Stephanie; Kaul, Arvind; Moriarty, Andrew Stephen; Perros, Petros; Sampford, James; Smith, Natalie; Elfeddali, Iman; et al.
Abstract : Objectives: This study establishes research priorities for medically not yet explained symptoms (MNYES), also known as persistent physical symptoms or medically unexplained symptoms, from the perspective of patients, caregivers and clinicians, in a priority setting partnership (PSP) following the James Lind Alliance (JLA) approach. Research into such symptoms in general has been poorly funded over the years and so far has been primarily researcher-led with minimal input from patients, caregivers and clinicians; and sometimes has been controversial. Design: JLA PSP method. The PSP termed these symptoms MNYES. Methods: The study was conducted according to the JLA's detailed methodology for conducting priority setting exercises. It involved five key stages: defining the appropriate term for the conditions under study by the PSP Steering Group; gathering questions on MNYES from patients, caregivers and clinicians in a publicly accessible survey; checking these research questions against existing evidence; interim prioritisation in a second survey; and a final multi-stakeholder consensus meeting to determine the top 10 unanswered research questions using the modified nominal group methodology. Results: Over 700 responses from UK patients, caregivers and clinicians were identified in the two surveys and charities contributed from a broad range of medical specialties and primary care. The final top 10 unanswered research questions cover, among others: treatment strategies, personalisation of treatment, collaborative care pathways, training for clinicians and outcomes that matter to patients. Interpretation: The top 10 unanswered research questions are expected to generate much needed, relevant and impactful research into MNYES.